2020
DOI: 10.3344/kjp.2020.33.3.258
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of ultrasound guidedversusblind genicular nerve block on pain, muscle strength with isokinetic device, physical function and quality of life in chronic knee osteoarthritis: a prospective randomized controlled study

Abstract: Background The genicular nerve block (GNB) is demonstrated from several reports to alleviate pain and improve knee functionality in patients with chronic knee osteoarthritis (OA). Ultrasound (US)-guided GNB has been the most used imaging method. This study aimed to compare the effectiveness of US-guided versus blind GNB in the treatment of knee OA. Methods This prospective, randomized clinical trial included patients with knee OA based on American College of Rheumatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…On the other hand, ultrasound-guided GNB is an emerging treatment option that aims to control pain by inhibiting knee innervation. A recent study comparing ultrasound-guided versus blinded GNB injections revealed the superiority of ultrasoundguided injections in improving the functionality in KOA patients [25]. Thus, our functional improvement findings can also be attributed to precision attained by the ultrasound-guided administration of the anaesthetic solution.…”
Section: Discussionsupporting
confidence: 54%
“…On the other hand, ultrasound-guided GNB is an emerging treatment option that aims to control pain by inhibiting knee innervation. A recent study comparing ultrasound-guided versus blinded GNB injections revealed the superiority of ultrasoundguided injections in improving the functionality in KOA patients [25]. Thus, our functional improvement findings can also be attributed to precision attained by the ultrasound-guided administration of the anaesthetic solution.…”
Section: Discussionsupporting
confidence: 54%
“…In another study, it was observed that patients with knee osteoarthritis and US-guided injection had a worse quality of life at 3 months than patients with palpation-guided injections, while walking and standing tests were better in the former than in the latter group. 55 All four studies comparing US and fluoroscopy guidance of intervention revealed no difference concerning the nine efficacy outcomes assessed (six outcomes with moderate, three with high RoB). 12 13 15 16 In contrast, one study comparing US or fluoroscopy versus palpationguided injections reported a higher patient satisfaction and patients' judgement of treatment efficacy in the US/ fluoroscopy as compared with the palpation group.…”
Section: Efficacymentioning
confidence: 88%
“…GNB is a relatively novel technique developed to relieve chronic OA related pains with reported high efficacy [20]. Ultrasound guided GNB showed more effective clinical results when compared to blind injections in a randomized clinical trial of 40 patients [12]. Furthermore, Kim et al [13] compared the efficacy of GNB when performed with ultrasound and with fluoroscopy in a series of 61 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Egyptian Journal of Radiology and Nuclear Medicine improve functional capacity mainly on short term bases as evidenced by many studies [9][10][11]. Genicular nerve block (GNB) has recently emerged as an alternative technique with very promising results to reduce OA related pains and improve functional status as evidenced by many recent studies [1,12,13]. It's based on the fact that genicular nerves are accompanied with genicular arteries, which can be easily identified at certain anatomical land marks using ultrasound and confirmed with color Doppler [1].…”
Section: Open Accessmentioning
confidence: 99%